Association Between Tuberculosis Knowledge and Anxiety Levels Among Patients with Pulmonary Tuberculosis - Yuyun Nailufar; Setiyo Adi Nugroho (Genius Publishing (CV. Gerbang Ilmu Nusantara), 2025)
Introduction: Tuberculosis (TB) remains a major public health problem in many developing countries, including Indonesia. Limited patient knowledge about the disease may influence psychological responses, including anxiety during treatment. Understanding the relationship between knowledge and anxiety is important to improve patient outcomes.Objectives: This study aimed to determine the level of knowledge about pulmonary tuberculosis, assess anxiety levels among patients, and analyze the relationship between tuberculosis knowledge and anxiety levels.Methods: This study employed a quantitative correlational design with a cross-sectional approach. A total of 148 patients with pulmonary tuberculosis undergoing treatment were included using a total sampling technique. Data were collected using structured questionnaires assessing knowledge and anxiety levels. Statistical analysis was performed using the Spearman rank correlation test with a significance level of p < 0.05.Results: The findings showed that most patients had a moderate level of knowledge and experienced moderate levels of anxiety. Statistical analysis revealed a significant relationship between patients’ knowledge and anxiety levels (p = 0.001), with a negative correlation coefficient (r = -0.482), indicating that higher levels of knowledge were associated with lower levels of anxiety.Conclusions: There was a significant relationship between tuberculosis knowledge and anxiety levels among patients. Improving patient knowledge may contribute to reducing anxiety during tuberculosis treatment.